PERAN KOMPENSASI SEBAGAI VARIABEL MODERASI PADA PENGARUH DISIPLIN KERJA TERHADAP KINERJA KARYAWAN - Dunggio, Maryam; Chusnah, Chusnah; Sukatmajaya, Ahmad; Maulidiya, Aufia (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
This study aims to analyze the effect of work discipline and compensation on employee performance. In addition, this study aims to test the moderation effect of compensation variables in strengthening the influence of work discipline on employee performance. The study was conducted using a sample of 67 employees of the production department at PT. SS Danisa Nusantara. The data analysis method in this study used the SEM-PLS model. The results of the study proved that work discipline has a positive and significant effect on employee performance. Compensation has no significant effect on employee performance. The results of moderation effect testing showed that interaction had no significant effect on employee performance. Therefore compensation can be expressed as a moderator homologizer variable, which has the potential to become a moderating variable.